Reconstructing Tolerance Education Through a Co-curricular “Social Laboratory”: A Theoretical Review of Intergroup Contact and Sosial Learning - Sarif Hidayat; Prayoga Bestari; Asep Mahpudz (Universitas Lambung Mangkurat, 2026)
Contemporary tolerance education in Indonesia faces a fundamental challenge: the discrepancy between the idealism of an inclusive curriculum and the reality of an increasingly polarized society. This article aims to reconstruct character education approaches by proposing a co-curricular-based